10 kHz spinal cord stimulation for the treatment of non‐surgical refractory back pain: subanalysis of pooled data from two prospective studies - Al‐Kaisy, A.; Van Buyten, J. P.; Kapural, L.; Amirdelfan, K.; Gliner, B.; Caraway, D.; Subbaroyan, J.; Edgar, D.; Rotte, A. (Anaesthesia, 2020)
Summary Spinal cord stimulation at 10 kHz is a promising therapy for non‐surgical refractory back pain; however, published data are currently limited. We present a subanalysis of prospectively collected clinical outcome data for non‐surgical refractory back pain patients treated with 10 kHz spinal cord stimulation, from the independent cohorts of two previous studies (SENZA‐RCT and SENZA‐EU). Clinical outcomes were evaluated at pre‐implantation (baseline), 3 months, 6 months and 12 months following 10 kHz spinal cord stimulator implantation. These included: pain relief; responder rate (≥ 50% pain relief from baseline); remission rate (VAS ≤ 3.0 cm); disability (Oswestry Disability Index(ODI)); and opioid use. At 3 months, average back pain decreased by 70% in the combined cohort (60% in the SENZA‐RCT and 78% in the SENZA‐EU cohorts). This was sustained at 12 months, with a 73% back pain responder rate and 68% remission rate in the combined cohort. Leg pain relief results were generally comparable to those for back pain relief. At 12 months, the combined cohort had an average decrease in ODI scores of 15.7% points from baseline and opioid use more than halved. In conclusion, 10 kHz spinal cord stimulation reduced pain, disability and opioid consumption in non‐surgical refractory back pain subjects. Application of this therapy may improve the care of non‐surgical refractory back pain patients and reduce their opioid consumption.